Chemical characterization, antimicrobial activity and toxicity of essential oils of Pimenta dioica L. and Citrus sinensis L. Osbeck (Research, Society and Development, 2020)
This study evaluated the toxicity and antimicrobial activity in the face of Escherichia coli and Staphylococcus aureus of essential oils of Pimenta dioica Lindl. and Citrus sinensis L. The essential oils (EOs) were extracted by hydrodistillation, with chemical characterization by gas chromatography coupled and mass spectrometry (GC-MS). Physicochemical parameters were determined according to the Brazilian Pharmacopeia. The toxicity test followed the bioassay with Artemia salina Leach, the EOs approved in this assay followed to evaluate its biological properties. The antimicrobial activity followed the methodology described by the Clinical and Laboratory Standards Institute using the Disc Diffusion Method, Broth Dilution for Minimum Inhibitory Concentration (MIC) and subsequent minimum bactericide concentration for to evaluate the action of EOs against E. coli and S. aureus. Both EOs showed low toxicity, and thus were evaluated for the biological antimicrobial properties. Both EOs presented bactericidal potential against the microorganisms tested, showing satisfactory results for their action. The results indicate that the evaluated EOs are composed of substances that provide and encourage their application due to their potential for antimicrobial biological activity.